Food and feeding habits of the exotic fish Oreochromis mossambicus (Peters, 1852) from a tropical reservoir of Chalakudy River, Kerala - Roshni, K.; Renjithkumar, C. R.; Madhusoodana Kurup, B. (Indian Journal of Fisheries, 2016)
The diet composition of the exotic fish, Oreochromis mossambicus (Peters, 1852) was studied in Poringalkuthu Reservoir, Kerala from June 2011 to May 2012. O. mossambicus (2.52 t) forms a regular fishery which indicate that the fish has been established successfully in the reservoir. Gut content analysis revealed detritus to be the dominant food item followed by chlorophyceae, cyanophyceae, bacillariophyceae, zooplankton, plant matter, sand particles, fish parts, insects and miscellaneous items. The present study shows that the species is an omnivore, with a euryphagous feeding habit.